Understanding Health Insurance Accessibility for People Living with HIV/AIDS in Kathmandu Valley: Barriers, Attitudes and Policy Recommendations - Ranjit, Regan; Adhikari, Nanda K.; Rijal, Barsha; Ranjit, Swechchha (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2026)
This study explores how accessibility and effectiveness Nepal’s free health insurance scheme for people living with HIV/AIDS (PLHIV) in Kathmandu Valley, using a mixed-method approach with both quantitative and qualitative data. A survey of 150 PLHIV, along with 25 in-depth interviews and 4 focus group discussions (FGDs), were conducted to gather insights into participant’s experiences, perceptions and the barriers they face. The findings reveal that the health insurance program provides significant financial relief, making healthcare more accessible to PLHIV by reducing out-of-pocket expenses for essential services. However, there are notable gaps in the program’s coverage, particularly for mental health, chronic disease management and specialized treatments. These limitations prevent the program from fully meeting the diverse healthcare needs for PLHIV which is essential for improving their long-term well-being. In addition to coverage gaps, the study identifies several systemic barriers that hinder the program’s effectiveness. Social stigma and discrimination remain significant obstacles, with many PLHIV expressing concerns about being identified and facing negative attitudes from healthcare providers for the community. These concerns discourage participation in the program and limit access to care. Furthermore, operational inefficiencies, such as delay in service delivery, breaches of confidentiality during referrals and bureaucratic barriers to enrollment, further undermine the program’s impact. The study recommends expanding the insurance coverage to include mental health and chronic disease care, improving service delivery by addressing referral system issues, streamlining enrollment processes and implementing stigma-reduction initiatives to create a more supportive healthcare environment for PLHIV. These measures could significantly enhance the program’s accessibility, exclusivity and overall effectiveness.